Implementation of Character Education Based on the Al-Qur’an and Hadith - Huda, Miftahul; Palupi, Retno (Journal of Innovation in Teaching and Instructional Media, 2024)
The aim of study is to form students with character by becoming individuals who are faithful, responsible, honest, disciplined and have high social awareness. Study was carried out by observing the Islamic boarding school environment which was strengthened by library research. Observations were carried out through student learning activities, both formal and non-formal. The results of this study were an increase and renewal of the character values ​​of students, in the form of actualizing the values ​​of honesty, caring, cooperation and responsibility for the tasks they receive. The advantages of this study are not only providing an example from teachers to students but also implementing a curriculum and learning strategies based on the Qur’an and Hadith. This study contributes to existing learning strategies in institutions by integrating them with the Al-Qur’an and Hadith.